Sistem Pendukung Keputusan untuk Pengalokasian Dana Bantuan di Kelurahan Kebagusan dengan Metode Simple Additive Weighting (SAW) - Indah Febriyanti; Aan Risdiana; Achmad Birowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The problem faced by Kelurahan Kebagusan is that there is no structured system in determining the allocation of aid funds to the community, so the distribution process is often uneven and less targeted. So far, the determination of aid recipients is only based on subjective observations and manual assessments that have the potential to cause ineffectiveness in decision making. Therefore, a decision support system was designed to assist the kelurahan in prioritizing beneficiaries objectively and transparently. This system uses the Simple Additive Weighting (SAW) method, which allows the assessment process to be carried out based on the weights of several predetermined criteria, such as economic conditions, number of dependents, employment status, and home ownership. The result of this system development is a desktop-based application using the Java programming language, which is expected to help the kelurahan in managing data and performing calculations quickly and accurately, so that the allocation of aid funds can be more targeted and fair. Keywords: Decision Support System, Simple Additive Weighting, Fund Allocation, Kebagusan Village.